DAY OF THE WEEK EFFECT AND STOCKMARKET VOLATILITY: FURTHER EVIDENCE FROMMALAYSIA EXCHANGE - Zainudin Arsad; Mohd Shahrizan Othman (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2004)
This paper examines the day of the week anomalies at the Malaysian Exchange during various economic situations. Inparticular, the paper looks at the existence of day of the week effect for various indices, the popular benchmark CompositeIndex, the broader based Emas Index, smaller capital based Second Board Index, Financial Index of the Main Board andone of the newly created sectoral index of Trade and Services. Three estimation models are used to investigate thepresence of daily effect in these indices: the Ordinary Least Squares regression (OLS), Box and Jenkins ARIMA and theGARCH(p,q) models for capturing changing volatility in the stock returns. The OLS results reveal negative Monday meanreturns for each of the indices for the whole sample period. As expected during the Asian Economic Crisis period, themean returns are negative for each day of the week, with Thursday recording the largest negative returns. Negative meanreturns on Monday are not generally observed for each of the indices in recent years (during the World Economic Crisisand the following Recovery Period). When the changing volatility in the financial market is taken into account, theMonday negative returns remain significant during the whole sample period.